Gut Microbiota Features in Young Children With Autism Spectrum Disorders - Coretti, Lorena; Paparo, Lorella; Riccio, Maria Pia; Amato, Felice; Cuomo, Mariella; Natale, Alessandro; Borrelli, Luca; Corrado, Giusi; De Caro, Carmen; Comegna, Marika; Buommino, Elisabetta; Castaldo, Giuseppe; et al. (Frontiers in Microbiology, 2018)
Abstract Proliferation and/or depletion of clusters of specific bacteria regulate intestinal functions and may interfere with neuro-immune communication and behavior in patients with autism spectrum disorder (ASD). Consistently, qualitative and quantitative alteration of bacterial metabolites may functionally affect ASD pathophysiology. Up to date, age-restricted cohort studies, that may potentially help to identify specific microbial signatures in ASD, are lacking. We investigated the gut microbiota (GM) structure and fecal short chain fatty acids (SCFAs) levels in a cohort of young children (2-4 years of age) with ASD, with respect to age-matched neurotypical healthy controls. Strong increase of Bacteroidetes and Proteobacteria and decrease of Actinobacteria was observed in these patients. Among the 91 OTUs whose relative abundance was altered in ASD patients, we observed a striking depletion of Bifidobacterium longum, one of the dominant bacteria in infant GM and, conversely, an increase of Faecalibacterium prausnitzii, a late colonizer of healthy human gut and a major butyrate producer. High levels of F. prausnitzii were associated to increase of fecal butyrate levels within normal range, and over representation of KEGG functions related to butyrate production in ASD patients. Here we report unbalance of GM structure with a shift in colonization by gut beneficial bacterial species in ASD patients as off early childhood.